Studi Esensi Itsbat Nikah Di Pengadilan Agama Ditinjau Dari Hukum Perkawinan - Rahmi, Adinda Lailatul; Mairul, Mairul (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to criticize the essence of marriage law in religius courts because with the passing of the merriage law number 1 of 1974, marriage that are considered valid are marriages that have been registered. So, to occomodate marriages before the enactment of the 1974 marriage law, marriage orders were carried out in religius courts. But to this day the itsbat for marriage in religius courts still applies. To sharpen this research we formulate 1) what is the courts authority in matter of marriage itsbat and the essence of marriage itsbat, 2) what is the legal certainty regarding marriage itsbat in religius courts. The method used in this research is a nomative juridical method of collecting reseacrh materials aimed at writen documents, legal or reseacrh materials which are anayzed qualitativelyto answer the problems being studied. Based on the research results, it was found that there is legal disharmony, meaning that a marriage, but in one of the roles of the religius courts, it provides space for itsbat, meaning there is room for unregistered marriage to occur.